2010
DOI: 10.1186/1465-9921-11-16
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cytokine and nitric oxide by mesenchymal stem cell transfer in lung injury/fibrosis

Abstract: BackgroundNo effective treatment for acute lung injury and fibrosis currently exists. Aim of this study was to investigate the time-dependent effect of bone marrow-derived mesenchymal stem cells (BMDMSCs) on bleomycin (BLM)-induced acute lung injury and fibrosis and nitric oxide metabolites and inflammatory cytokine production.MethodsBMDMSCs were transferred 4 days after BLM inhalation. Wet/dry ratio, bronchoalveolar lavage cell profiles, histologic changes and deposition of collagen were analyzed.ResultsNitri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
0
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(142 citation statements)
references
References 43 publications
6
128
0
8
Order By: Relevance
“…Although some studies have demonstrated the therapeutic potential of bone marrow-derived stem cells in rodent lung injury models [23,[26][27][28], there is no evidence of a role for these stem cells in populating the lung alveolar epithelium in vivo [29][30][31][32]. Recent studies have reported efficient and direct derivation of lung alveolar epithelium from murine embryonic stem cells (ESCs) [10,11,14,16] for in vitro and in vivo applications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some studies have demonstrated the therapeutic potential of bone marrow-derived stem cells in rodent lung injury models [23,[26][27][28], there is no evidence of a role for these stem cells in populating the lung alveolar epithelium in vivo [29][30][31][32]. Recent studies have reported efficient and direct derivation of lung alveolar epithelium from murine embryonic stem cells (ESCs) [10,11,14,16] for in vitro and in vivo applications.…”
Section: Discussionmentioning
confidence: 99%
“…This effect was considered to occur in a paracrine manner, and to be mediated by reductions in nuclear factor kB activity and neutrophil accumulation [41]. Transfer of MSCs also reduced BLM-induced lung injury and fibrosis partly through downregulation of inflammatory cytokines, such as TNF-a and IL-6 [23]. However, our data showed that To our knowledge, this is the first report of the threedimensional alveolar lung structure regenerative potential and lung injury therapeutic potential of differentiated mouse iPSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under certain circumstances, MSCs can differentiate into chondrocytes, myoblasts, endothelial cells, epithelial cells, and neurocytes [9]. Furthermore, MSCs have been observed to display immunomodulatory properties [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating data obtained from animal studies has identified the curing role of stem cells in experimental lung fibrosis. Intravenous injection of bone marrow-derived mesenchymal stem cells (BM-MSCs) significantly reduced bleomycin-induced increase in wet/ dry ratio, degree of neutrophilic infiltration, collagen deposition, and levels of the cytokines and nitric oxide [50]. Another study indicates that intravenous mesenchymal stem cell transfer reduces bleomycin injectioninduced expressions of TGF-beta1, PDGF-A, PDGF-B, and IGF-1 mRNA, and that some MSC engrafts presenting in injured lung tissue are positive for pan-cytokeratin staining, which indicates the differentiation of MSCs into alveolar epithelial cells in vivo [51].…”
Section: Preclinical Studies Of Stem Cells In Pulmonary Fibrosismentioning
confidence: 99%